The Influence of Health Education About Pregnancy Exercises Using Audio Visual Media on The Interest of Pregnant Women at The Permata Hati Karanganyar Clinic - Ajeng Maharani; Aris Prastyoningsih; Frieda Ani Noor; Erlyn Hapsari; Kristina Maharani; Qomariyah Qomariyah (Syntax Corporation Indonesia, 2023)
Pregnancy exercise is a form of exercise or structured training. Regular exercise will improve blood circulation, strengthen muscles and stretch joints and can reduce disorders that commonly occur during pregnancy such as aches, back pain, stiff muscles, constipation, and reduce swelling of the legs. Doing regular pregnancy exercises can reduce lower back pain, one of which is by kneeling movements, rotating the pelvis, bending the buttocks, bending the knees, chest. The aim of this research is to determine the influence of health education about pregnancy exercise using audio visual media on the interest of pregnant women at the Permata Hati Karanganyar Clinic. This research is quantitative research with the form of a preliminary experimental design. This research method is pre-experimental research with a one-group-pretest-posttest design. The sample consisted of 32 respondents. The techniques used for this analysis are univariate and bivariate. Based on the Wilcoxon test results, a p-value of 0.000 < 0.05 so it can be concluded that there is a significant influence of providing health education about pregnant women's exercises using audio-visual media on the interest of pregnant women.